Holy Prophet (ﷺ) as a Military Commander and War Strategist; A Historical Analysis - Umme Aaimen; Dr. Anum Hameed; Maryam Ghazanfar; Muntaha Shahid (Social Science Review Archives, 2025)
The history of the world has seen that whether it is peace or war, it requires distant arrangement and multidimensional strategies. Life of Holy Prophet (ﷺ) is a role model for entirety of humanity; not just believers or followers. In contemporary era, challenges of war and peace among nations have taken a front seat in the global theatre. In the midst of this chaos, one would naturally want to look out for ideals and ideologies promoting better practices and strategies than there are in present. The Seerah of Holy Prophet (ﷺ) offers us just that. Holy Prophet (ﷺ) maintained His (ﷺ) message of Peacekeeping and upholding of justice even in the most chaotic of situations. His (ﷺ) life is filled with missions around war and peace and His exemplary character as a military commander and a war strategist. In addition to winning numerous wars like Badr, Uhud, and Khandaq through strategic thinking, the Holy Prophet (ﷺ) was also a kind-hearted military leader who worked toward lasting peace. His understanding of human nature and life itself, as well as His ability to adapt quickly to changing conditions, predict enemy tactics with a little insight, and uplift soldiers with his goals and ideas of justice, are still relevant in today military operations, which are never religiously tolerant until they kill every member of every weak group, during which settling for peaceful coexistence has been defined over an extended period of time. This study uses historical accounts to demonstrate how modern military leaders can learn from the Prophet strategies, which help them and mankind succeed.